1996
DOI: 10.1007/bf01664737
|View full text |Cite
|
Sign up to set email alerts
|

Predictive and concurrent validity of the Suicidal Ideation Questionnaire among American Indian adolescents

Abstract: Suicide is currently the second leading cause of death for ages 15-24 years; reports indicate that 6-8% of American teens have attempted suicide. Rates of suicide and suicide attempts are at least as high, if not higher, for American Indian adolescents and young adults. The Suicidal Ideation Questionnaire (Junior High School Version) (SIQ-JR) could be used to identify young people who may be at risk for attempting suicide, since this questionnaire focuses on suicidal ideation, a major risk factor for suicide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 12 publications
1
59
0
Order By: Relevance
“…In a small but unique study, the SIQ-JR was used to predict suicidality in the context of a very intense epidemic of suicidal behavior over the short term. It attained sensitivity of 0.80, specificity of 0.86, and a positive predictive value of 27% when using a future attempt as the criterion (Keane et al, 1996), but it is not clear how this would generalize to a less-acute community sample.…”
Section: Discussionmentioning
confidence: 97%
“…In a small but unique study, the SIQ-JR was used to predict suicidality in the context of a very intense epidemic of suicidal behavior over the short term. It attained sensitivity of 0.80, specificity of 0.86, and a positive predictive value of 27% when using a future attempt as the criterion (Keane et al, 1996), but it is not clear how this would generalize to a less-acute community sample.…”
Section: Discussionmentioning
confidence: 97%
“…Only one, supportive, validation study of a standard early adolescent risk measure was identified (Keane, Dick, Bechtold, & Manson, 1996). Brief (sometimes single item) ideation, attempt, and likelihood questions very similar to those of the SRQ, have, however, received wide use in studies of American Indians of varying tribal affiliations and age groups (e.g., Blum, Harmon, Harris, Bergeisen, & Resnick, 1992;Dinges & Duong-Tran, 1993Grossman, Milligan, & Deyo, 1991;HowardPitney, LaFromboise, Basil, September, & Johnson, 1992;Norton, Rockman, Malan, Cox, & Hewitt, 1995).…”
Section: The Suicidal Risk Questionnairementioning
confidence: 99%
“…Reliability of the SIQ-JR is high, ranging from 0.91 to 0.96 [40][41][42] for internal consistency and from 0.87 to 0.93 for test-retest reliability (0.89 overall; 0.87 for adolescent girls and 0.93 for adolescent boys). 42 The SIQ-JR has demonstrated criterion validity, 22,40,42,43 construct validity in community 41,42,[44][45][46][47] and Interim Depression and Suicidal Ideation. During the second survey, 2 questions directly assessed participants' subjective experiences of depression and suicidal ideation after the first survey: "Since the first survey, have you felt depressed?…”
Section: Outcome Measuresmentioning
confidence: 99%